KERAJINAN TRADISIONAL BALI SEBAGAI ELEMEN BUDAYA DAN DAYA TARIK WISATA - JKI, Admin (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2017)
Bali is a world-class tourist destination. Regional economic structure of Bali comes from the tourism sector. Traditional crafts as Balinese cultural products have existed for generations and have developed through the dynamics of culture. In the development of tourism, the crafts packaging becomes the economic resources although initially it was made more for social and practical purposes. The objective of the research is to encourage public appreciation for traditional crafts as well as to enhance their existence as tourist attractions. Data collection is done through survey and interview with descriptive-qualitative analysis approach. The findings show that Balinese traditional handicrafts turn out to be a commodity in the form of souvenirs (goods) and services in the tourism industry. This commodity has a great market opportunity, consequently it can produce income for the society. A handicraft becomes a cultural product and a tourist attraction because it can be seen (something to see), it can be bought (something to buy) as a souvenir, and it shows activities that can be done (something to do). Craftsmen in Bali create contemporary handicrafts so as to meet the needs of the tourism industry. This strategy is also made to encourage people’s appreciation for Balinese traditional handicrafts as well as to enhance their existence. Related to social needs, craftsmen are expected to maintain the Balinese cultural values and meanings in every traditional craft.